Are we in sync? How industry practitioners and academics profile managerial competencies: A study of an Association to Advance Collegiate Schools of Business–accredited business school in Hong Kong. Issue 3 (3rd April 2017) - Ko, Stephen; Chan, Simon C. H.
ABSTRACT: The authors draw on the taxonomy of managerial competencies to assess the alignment of perceptions between industry practitioners and business academics when profiling managerial competencies required for effective performance in workplaces. Findings show that the set of managerial competency profiles, as viewed by practitioners, generally fit well with the perceptions of business academics as represented in the intended learning outcomes specified in the undergraduate business programs. It suggests that the targeted managerial competencies built around business curricula are largely in sync with the expectations of practitioners. Implications for theory and practice are discussed.